2021
DOI: 10.17711/sm.0185-3325.2021.010
|View full text |Cite
|
Sign up to set email alerts
|

Emotional distress and its care in empowered indigenous women exposed to domestic violence and the demands of child rearing

Abstract: Introduction. Indigenous girls and women in Mexico suffer emotional distress due to marital violence and adherence to gender roles. They are unlikely to denounce violence or treat their health in a timely manner. Women can cope with their distress by participating in empowerment processes. Objective. Describe in indigenous empowered women the emotional distress caused by domestic violence in their childhood and the current demands of raising their children and the actions they take to cope with them. Method. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…The resilience, creativity, and adaptative capacity of indigenous women was also reported in studies prior to the pandemic (Vega, Gutiérrez, Fuentes de Iturbe, & Rodríguez, 2021). They showed that women victims of domestic violence can use these survival social networks to listen and talk about their emotional distress, such as sadness, worry, nervousness, and irritability (Vega et al, 2021). These are some of the self-care resources (such as social networks on the Internet, traditional medicine, and family care) that people and groups implement to diagnose, explain, care for, control, relieve, endure, cure, solve, and prevent the processes affecting their health (Menéndez, 2009).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The resilience, creativity, and adaptative capacity of indigenous women was also reported in studies prior to the pandemic (Vega, Gutiérrez, Fuentes de Iturbe, & Rodríguez, 2021). They showed that women victims of domestic violence can use these survival social networks to listen and talk about their emotional distress, such as sadness, worry, nervousness, and irritability (Vega et al, 2021). These are some of the self-care resources (such as social networks on the Internet, traditional medicine, and family care) that people and groups implement to diagnose, explain, care for, control, relieve, endure, cure, solve, and prevent the processes affecting their health (Menéndez, 2009).…”
Section: Introductionmentioning
confidence: 65%
“…They engaged in subsistence agriculture, bartering, manufacturing face masks, loans, marketing, and exhibitions in online social networks, as well as seeking government support (Del Carpio et al, 2021). The resilience, creativity, and adaptative capacity of indigenous women was also reported in studies prior to the pandemic (Vega, Gutiérrez, Fuentes de Iturbe, & Rodríguez, 2021). They showed that women victims of domestic violence can use these survival social networks to listen and talk about their emotional distress, such as sadness, worry, nervousness, and irritability (Vega et al, 2021).…”
Section: Introductionmentioning
confidence: 82%